Analisis Reaksi Pasar Modal dilihat dari Abnormal Return (AR) dan Trading Volume Activity (TVA) terhadap Kebijakan Tax Amnesti pada Saham Perusahaan yang terdaftar di Saham Indeks LQ 45 - Isa Arief Alhakim; Setyowati Subroto (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2017)
The purpose of this study is 1) To determine whether there are differences abnormal return on the shares listed in the LQ 45 index 2). To find out if there is any difference in trading volume of activity on stocks listed in index LQ 45. Data collection method used in this research is Documentation. While the data analysis method used is the test analysis of difference of two average. The results of this study prove that, statistical test results show the probability of events of 0.205. The probability obtained is greater than 0.05 so it can be concluded that there is no difference between abnormal returns between before and after the tax amnesty policy, thus the hypothesis which states "There is a difference in abnormal returns in the issuers of the LQ45 index before and after the tax amnesty policy" is not acceptable the truth. Statistical test results show the probability of an event is 0.311. The probability obtained is greater than 0.05 so it can be concluded that there is no difference between trading volume activity between before and after the tax amnesty policy, thus the hypothesis states "There is a difference in trading volume activity in the issuers of the LQ45 index before and after the tax amnesty policy" no the truth can be accepted.